Effects of Intestinal Flora on Irritable Bowel Syndrome and Therapeutic Significance of Polysaccharides - Ye, Yang; Liu, Yanan; Cheng, Kejun; Wu, Zufang; Zhang, Peng; Zhang, Xin (Frontiers in Nutrition, 2022)
In recent years, the relevant research on intestinal flora has been in full swing, and it has become an extremely important research direction in clinical medicine and life science. Irritable bowel syndrome (IBS) is a common disease characterized by changes in intestinal function and accompanied by comorbid anxiety. At present, the pathogenic mechanism of IBS is not yet clear. The gut-brain axis (GBA), as a two-way information exchange system between the gut and the brain, has an important influence on the prevention of IBS. Present studies have shown that polysaccharides are important for maintaining the steady status of intestinal micro-environment. This review summarized the relationship between intestinal flora, GBA and immune activation, and provided a new idea for the preventive treatment of IBS from the perspective of polysaccharides..